Heterogeneous and overlapping mechanisms of myocardial ischemia in patients with ischemia and non-obstructive coronary arteries. Preliminary results from the MOSAIC-COR Registry. (3rd October 2022) - Szolc, P S; Niewiara, L; Legutko, J; Kleczynski, P; Rzeznik, D; Tekieli, L; Podolec, J; Diachyshyn, M; Stapor, M; Zmudka, K; Guzik, B
Abstract: Background: Patients with ischemia and non-obstructive coronary arteries (INOCA) account for 30–70% of all patients undergoing elective coronary angiography for angina. In these group of patients various mechanisms may be responsible for myocardial ischemia, including increased microvascular resistance, epicardial spasm or microvascular spasm. There are limited data on the prevalence and coexistence of different mechanisms in patients with INOCA. Purpose: The primary objective was to assess the occurrence of coronary microcirculatory disease (CMD), epicardial vasospastic angina (EVSA), microvascular vasospastic angina (MVSA) and their coexistance in patients with INOCA. The secondary objective was the analysis of subgroups' clinical characteristics. Methods: This was a single-center, prospective, observational study. In the absence of significant coronary artery stenosis, a complex functional coronary assessment was performed. Values of fractional flow reserve (FFR), RFR, coronary flow reserve (CFR) and index of microcirculatory resistance (IMR) were determined. Coronary artery and microvascular vasoreactivity was tested using the provocative acetylcholine test. Results: We enrolled 90 consecutive patients with INOCA. Overlapping of CMD and CMD/EVSA phenomenon was observed. Accordingly, we distinguished 6 subgroups of INOCA patients in comparison to the CorMicA trial. Mixed pathophysiology (CMD+EVSA and CMD+MVSA) was diagnosed in 33% of patients. In the CMD+EVSA subgroup, 73% of subjects were male, while in the CMD+MVSA only 7.1% were male (p=0.005). Typical cardiovascular risk factors were common in the whole INOCA group. Conclusions: The INOCA population is a heterogeneous group with various pathophysiology of myocardial ischemia. Overlapping of different pathomechanisms is a frequent phenomenon, which has to be consider for treatment optimization and future research. Funding Acknowledgement: Type of funding sources: None.